Declining Trend of Transapical Access for Transcatheter Aortic Valve Replacement in Patients with Aortic Stenosis. (19th September 2022) - Sohal, Sumit; Mehta, Harsh; Kurpad, Krishna; Mathai, Sheetal Vasundara; Tayal, Rajiv; Visveswaran, Gautam K.; Wasty, Najam; Waxman, Sergio; Cohen, Marc
Abstract : Introduction . The last decade has witnessed major evolution and shifts in the use of transcatheter aortic valve replacement (TAVR) for severe aortic stenosis (AS). Included among the shifts has been the advent of alternative access sites for TAVR. Consequently, transapical access (TA) has become significantly less common. This study analyzes in detail the trend of TA access for TAVR over the course of 7 years. Methods . The national inpatient sample database was reviewed from 2011–2017 and patients with AS were identified by using validated ICD 9-CM and ICD 10-CM codes. Patients who underwent TAVR through TA access were classified as TA-TAVR, and any procedure other than TA access was classified as non-TA-TAVR. We compared the yearly trends of TA-TAVR to those of non-TA-TAVR as the primary outcome. Results . A total of 3, 693, 231 patients were identified with a diagnosis of AS. 129, 821 patients underwent TAVR, of which 10, 158 (7.8%) underwent TA-TAVR and 119, 663 (92.2%) underwent non-TA-TAVR. After peaking in 2013 at 27.7%, the volume of TA-TAVR declined to 1.92% in 2017 (p < 0.0001 ). Non-TA-TAVR started in 2013 at 72.2% and consistently increased to 98.1% in 2017. In-patient mortality decreased from a peak of 5.53% in 2014 to 3.18 in 2017 (p = 0.6 ) in the TA-TAVR group and from a peak of 4.51% in 2013 to 1.24% in 2017 (p = 0.0001 ) in the non-TA-TAVR group. Conclusion . This study highlights a steady decline in TA access for TAVR, higher inpatient mortality, increased length of stay, and higher costs compared to non-TA-TAVR.